Distinct Effects of Milks From Various Animal Types on Infant Fecal Microbiota Through in vitro Fermentations - Li, Na; Li, Bailiang; Guan, Jiaqi; Shi, Jialu; Evivie, Smith Etareri; Zhao, Li; Huo, Guicheng; Wang, Song (Frontiers in Microbiology, 2020)
Human milk is compatible with infant intestinal microbiota, and is important for infant health. However, most infants do not receive sufficient exclusive breastfeeding and the effects of including other types of animal milk on gut microbiota of infants are unclear. Therefore, the objective of this study was to elucidate the effects of milks from various animal sources on infant fecal microbiota through in vitro fermentation. The types of milk assessed include cow milk, goat milk, camel milk, mare milk, human milk and infant formula milk. Here we determined the gas pressure, pH and microbiota after 24 h fermentation. Results showed that mare milk had the lowest gas pressure rating, with levels similar to human milk. More so, pH analysis demonstrated that other milk types were similar to human milk. Bacterial 16S rRNA gene sequence analysis revealed that all milk types increased the abundance of Bifidobacterium and Lactobacillus, which was proportional to the lactose content of milk. Moreover, mare milk also significantly increased the relative abundance of Akkermansia. Collectively, results from mare milk (gas pressure, pH and microbiota) were comparable to that of human milk, and thus support the theoretical basis for exploring the development of a mare milk-based infant formula.